Mobile Health untuk Mencegah Luka Diabetes: A Systematic Review - Risyda Zakiyah Hanim; Tuti Herawati (FORIKES, 2021)
Ulcus diabeticum is the most common complication that results in death. Diabetic foot currently reach 40 to 60 million people in patients diagnosed with diabetes mellitus. This article was a mobile-health systematic review in preventing diabetic foot injuries. The search sources were Scopus, Science Direct, PubMed, ProQuest, Ebscohost and Sage published from 2015 to 2020 with the search keywords of